STRATEGI GURU DALAM MENINGKATKAN KEMANDIRIAN SOSIAL ANAK TUNAGRAHITA RINGAN DI SDN BREBES 02 - Azizah, Nur; Toharudin, Moh; Sunarsiih, Diah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the strategies employed by teachers to enhance the social independence of students with mild intellectual disabilities at SDN Brebes 02. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation involving teachers and students in grades IV and V. In this study, triangulation was used to obtain the level of data absorption, and the type of data analysis employed was triangulation. The findings reveal that the main strategies implemented by teachers include cooperative learning, positive reinforcement (both verbal and nonverbal), social simulation activities, the use of instructional media, and collaboration with parents. These approaches have proven effective in improving students' social interaction, cooperation, and self-confidence. This study highlights the importance of ongoing teacher training and enhanced cross-sector collaboration to more effectively and sustainably support the development of social independence among students with mild intellectual disabilities.